2018
DOI: 10.5430/jnep.v8n8p53
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice related to reproductive health among female adolescents

Abstract: Objective: Reproductive health (RH) is a crucial aspect of general health; it is a reflection of health during adolescence and adulthood. The period of adolescence in females is a period of physical and psychological preparation for safe motherhood. As direct reproducers, adolescent girls' health influences not only their own health but also the health of the future generation. This study aimed to assess knowledge, hygiene practices during menses, and attitudes of female adolescents in Riyadh female secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
5
20
0
Order By: Relevance
“…This is because daughters have a trustworthy relationship with their mothers due to gender homogeneity [ 20 ]. Similarly, Gaferi et al [ 21 ] also explained the result of good communication between mothers and daughters by the fact that many mothers are being educated nowadays. Furthermore, Kumar and Srivastava [ 22 ] claimed that educated Indian mothers are not hesitant to talk about SRH issues, including menstruation, with their daughters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because daughters have a trustworthy relationship with their mothers due to gender homogeneity [ 20 ]. Similarly, Gaferi et al [ 21 ] also explained the result of good communication between mothers and daughters by the fact that many mothers are being educated nowadays. Furthermore, Kumar and Srivastava [ 22 ] claimed that educated Indian mothers are not hesitant to talk about SRH issues, including menstruation, with their daughters.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of restrictions related to menstruation also exist in other countries, such as India, Nepal, and Saudi Arabia [ 19 , 22 , 23 , 24 , 25 , 26 ]. The restrictions also include not serving food and attending guests [ 22 , 23 ], food restrictions [ 21 , 22 , 27 ], religious practices [ 22 , 23 , 24 , 27 ], sleeping on the bed or sitting on the sofa [ 22 ], and physical exercise [ 21 , 22 ]. In Bangladesh, the conventional practice rooted in the conservative socio-cultural structure has taught women that their desires, dreams, pains, aspirations, sorrows, and joys can never be expressed outside the home or in public.…”
Section: Discussionmentioning
confidence: 99%
“…However, sexual and reproductive health are considered to be socially sensitive issues in the Gulf regions. 10 organs. Reproductive health (RH) knowledge was unsatisfactory, as 66.3% of the participants had incorrect knowledge.…”
Section: Reproductive Health Knowledgementioning
confidence: 99%
“…9 Consequently, awareness about infertility and disorders such as PCOS may be low among Arab teenagers. 10 Studies conducted in Iran, Saudi Arabia, Oman, and Kuwait have reported PCOS prevalence rate of 6-9%. 11 However, no conclusive study indicating its prevalence or awareness of such a condition among Emirati women of UAE has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The adolescent has to educate in the early stage to protect their body and future from the improper social intercourse such as turn to the free sexual behavior, child marriage, sexual out of marriage, and sexual without protection that put them at risk to dangerous disease like HIV/AIDS. Improper knowledge about reproductive health among adolescents was not only found in Indonesia, a study in Riyadh reported that more than 60% of adolescents had inaccurate knowledge [19]. Audiovisual media, both online and offline, was proved as an effective media to deliver information to adolescents [20,21].…”
Section: Pre and Post-assessmentsmentioning
confidence: 99%